Early muscle and brain ultrastructural changes in polymerase gamma 1‐related encephalomyopathy. Issue 1 (27th April 2012) - Nolte, Kay W.; Trepels‐Kottek, Sonja; Honnef, Dagmar; Weis, Joachim; Bien, Christian G.; van Baalen, Andreas; Ritter, Klaus; Czermin, Birgit; Rudnik‐Schöneborn, Sabine; Wagner, Norbert; Häusler, Martin
<x xml:space="preserve">Abstract</x> Mutations affecting the mitochondrial DNA‐polymerase gamma 1 (POLG1) gene have been shown to cause Alpers‐Huttenlocher disease. Ultrastructural data on brain and muscle tissue are rare. We report on ultrastructural changes in brain and muscle tissue of two sisters who were compound heterozygous for the c.2243G>C and c.1879C>T POLG1 mutations. Patient 1 (16 years) presented with epilepsia partialis continua that did not respond to antiepileptic treatment. Neuroimaging showed right occipital and bithalamic changes. Light microscopy from a brain biopsy performed after 3 weeks suggested chronic encephalitis showing astro‐ and microgliosis as well as perivascular CD8‐positive T‐cells. However, immunosuppressive therapy failed to improve her condition. When her 17‐year‐old sister (patient 2) also developed epilepsy, an intensified search for metabolic diseases led to the diagnosis. On electron microscopy mitochondrial abnormalities mainly affecting neurons were detected in the brain biopsy of patient 1, including an increase in number and size, structural changes and globoid inclusions. In patient 2, light and electron microscopy on a muscle biopsy confirmed a mitochondrial myopathy, also revealing an increase in mitochondrial size and number, as well as globoid inclusions. Neurons may be the primary target of mitochondrial dysfunction in brains of patients with Alpers disease related to POLG1 mutations. During early disease stages, brain histopathology may be misleading, showing reactive inflammatory changes.